Effects of a Dual‐Frequency Frequency‐Sweeping Ultrasound Treatment on the Properties and Structure of the Zein Protein. Issue 2 (3rd December 2014) - Ren, Xiaofeng; Wei, Xun; Ma, Haile; Zhou, Huiji; Guo, Jingjing; Mao, Shuyun; Hu, An
Abstract : We investigated the effects of a dual‐frequency frequency‐sweeping ultrasound (DFFSU) treatment on the functional properties and structure of zein. The solubility of ultrasound‐treated zein proteins increased slightly but significantly as the treatment time increased. The results showed that the DFFSU treatment had an obvious influence on the mean particle size and the size distribution. A significant ( P < 0.05) increase in the size of the particles with respect to time was observed after a sonication time of more than 20 min in zein solutions. Differential scanning calorimetry results showed that sonication alters the thermal behavior of zein. Circular dichroism spectra showed a small increase in the percentage of ordered structure elements within the protein molecule. After 60 min of ultrasonication, the percentage of α‐helix structures increased by 0.9%, whereas the percentage of β‐sheets and β‐turns decreased by 0.5%. Microstructural analyses by scanning electron microscopy showed that several microholes appeared in the zein following ultrasonic pretreatment. Under the conditions investigated in this study, DFFSU treatment was found to affect the studied functional properties of the zein protein. This technology could be used to obtain improved functional properties in some protein samples.